(untitled) (Economics and region, 2021)
In the article, we examined the main trends in the implementation of financial innovations in the work of banking institutions and identified the prospects for their development in the coming years. We studied the benefits of using such technologies as digital banking, artificial intelligence, open banking, microservices, e-wallets, blockchain, etc. for the banking sector and users of banking services. We also determined how the use of modern technologies affects the strengthening of banking security and the efficiency and profitability of the banking business. We examined the global trends in the implementation of FinTech in banking and the impact of relevant technologies on the development of the Ukrainian banking sector. We discussed the role of the National Bank in the process of intensifying the implementation of Fintech in the banking sector of Ukraine.